2021
DOI: 10.1096/fj.202100074r
|View full text |Cite|
|
Sign up to set email alerts
|

GYY4137 protected the integrity of the blood‐brain barrier via activation of the Nrf2/ARE pathway in mice with sepsis

Abstract: Injury to the blood‐brain barrier (BBB) plays a vital role in sepsis‐associated encephalopathy (SAE), which is one of the most common complications of sepsis. GYY4137, a new synthetic compound of hydrogen sulfide (H2S), has extensive biological benefits. In this study, we focused on the protective effects of GYY4137 on the BBB in septic mice and the underlying mechanisms. The results suggested that whether administrated at the same time or 3 hours after LPS injection, GYY4137 both significantly alleviated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 57 publications
(110 reference statements)
2
12
0
Order By: Relevance
“…More recently, two studies have shown that the pretreatment of GYY4137 (25 mg/kg and 50 mg/kg intraperitoneal injection), a novel slow-releasing H 2 S donor, protected against acute lung injury caused by CLP-induced sepsis in mice [ 154 , 155 ]. A similar salutary effect of H 2 S was also reported in urinary-derived sepsis, pseudomonas aeruginosa sepsis and pneumococcal pneumosepsis, together with LPS-induced endotoxemia [ 21 , 156 , 157 , 158 , 159 ].…”
Section: Gaseous Mediators In Sepsis/septic Shocksupporting
confidence: 68%
“…More recently, two studies have shown that the pretreatment of GYY4137 (25 mg/kg and 50 mg/kg intraperitoneal injection), a novel slow-releasing H 2 S donor, protected against acute lung injury caused by CLP-induced sepsis in mice [ 154 , 155 ]. A similar salutary effect of H 2 S was also reported in urinary-derived sepsis, pseudomonas aeruginosa sepsis and pneumococcal pneumosepsis, together with LPS-induced endotoxemia [ 21 , 156 , 157 , 158 , 159 ].…”
Section: Gaseous Mediators In Sepsis/septic Shocksupporting
confidence: 68%
“…ML385, an inhibitor of Nrf2 [ 30 ], was used to further confirm whether the Keap1-Nrf2 pathway and its mediated antioxidative stress were involved in the protective effect of ICS on METH neurotoxicity. First, we focused on the effect of ML385, ICS, and METH on the Keap1-Nrf2 pathway and oxidative stress response.…”
Section: Resultsmentioning
confidence: 99%
“…Kelch-like ECH-associated protein 1 (KEAP1) is a regulatory protein that retains NRF2 in the cytoplasm and leads it to ubiquitination and proteasomal degradation. It is known that H 2 S donors can induce KEAP1 sulfhydration, a modification that leads to the NRF2 release, translocation to the nucleus, and promotion of gene transcription [ 26 , 37 , 38 , 39 , 40 ]. To determine whether GYY4137 affected the KEAP1 levels in basal conditions and in the context of RSV infection, the total cell lysates isolated from SAECs infected with RSV and treated with GYY4137 were analyzed by Western blot with anti-KEAP1 antibody.…”
Section: Resultsmentioning
confidence: 99%